Pengaruh Keterampilan Mengajar Guru dan Fasilitas Belajar Terhadap Motivasi Belajar Siswa Kelas XI Otkp SMK Nasional Bandung - Handayani, Nunik Dwi; Arief, Meta; Kurjono, Kurjono; Mulyadi, Hari (Universitas Pendidikan Ganesha, 2021)
The purpose of this study is to obtain information on the influence of teacher teaching skills and learning facilities on student learning motivation in Class XI OTKP SMK Nasional Bandung.The theory underlying this research is Maslow's self-actualization motivation theory. This research uses a quantitative approach with survey methods and instruments used in the form of questionnaires distributed class XI OTKP SMK Nasional Bandung as many as 105 respondents. Data analysis techniques use regression analysis. Research conducted on students of class XI OTKP SMK Nasional Bandung obtained the results that the condition of teaching skills, learning facilities against student learning motivation in the high category. The advice that can be given in this study is on the teacher's teaching skills variable to provide provision to educators with IHT, technical guidance and workshops that can improve the ability of teachers professionally as the most dominating variables. In the variables of learning facilities students in online learning can utilize gadgets and other facilities to create effective learning.